Synthesis and Characterization of IZO Composite Prepared by Sol-Gel Method - Halbos, Raghad J; Al-Algawi, Sariya; Rasheed, Rashed T (Al-Nahrain Journal of Science, 2018)
Indium oxide and indium zinc oxide composite (IZO) were prepared by sol-gel method and deposited on quartz substrate by dip coating technique. Two annealing temperatures (200 and 400◦C) and compositions were done. The structure and surface morphology of particles were characterized by X-ray diffraction (XRD), Atomic Force Microscope (AFM), FT-IR measurements. The XRD and AFM indicate decreasing in the particle size and improve of optical and electrical properties of composite with increasing of zinc oxide addition. The results of Hall measurements show that the In2O3 and its composite (IZO) have n-type.